Hard choices - Clinton, Hillary Rodham (New York : Simon & Schuster, 2014)
Hillary Clinton's candid reflections about the key moments during her time as Secretary of State, as well as her thoughts about how to navigate the challenges of the 21st century.
Part one: A fresh start. 2008: team of rivals ; Foggy bottom: smart power -- Part two: Across the Pacific. Asia: the pivot ; China: uncharted waters ; Beijing: the dissident ; Burma: the lady and the generals -- Part three: War and peace. Af-Pak: surge ; Afghanistan: to end a war ; Pakistan: national honor -- Part four: Between hope and history. Europe: ties that bind ; Russia: reset and regression ; Latin America: democrats and demagogues ; Africa: guns or growth? -- Part five: Upheaval. The Middle East: the rocky path of peace ; The Arab Spring: revolution ; Libya: all necessary measures ; Benghazi: under attack ; Iran: sanctions and secrets ; Syria: a wicked problem ; Gaza: anatomy of a cease-fire -- Part six: The future we want. Climate change: we're all in this together ; Jobs and energy: a level playing field ; Haiti: disaster and development ; 21st-Century statecraft: digital diplomacy in a networked world ; Human rights: unfinished business -- Epilogue.
Includes index.
Keywords: Clinton, Hillary Rodham; Obama, Barack; Stateswomen -- United States -- Biography; Cabinet officers -- United States -- Biography; United States -- Foreign relations -- 2009-; United States -- Politics and government -- 2009-